2013
DOI: 10.1123/japa.21.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Falling and Balance Ability in Older Men: The Priest Study

Abstract: Studies examining fear of falling among older adult men remain limited. The objectives of this study were to compare balance confidence in 2 age cohorts of older clergy and identify predictive determinants of balance confidence in a liturgical research initiative. Participants included 131 community-dwelling Roman Catholic priests age 60–97 yr living in religious communities in 10 mid-Atlantic states. Subjects completed the Activities-specific Balance Confidence Scale (ABC), Berg Balance Scale (BBS), timed up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
1
14
0
2
Order By: Relevance
“…These assistive devices enable functional independence and offer safety and confidence to the elderly, making it easier for them to carry out their daily activities. However, when not indicated or when used inappropriately, they can have the opposite effect and contribute to unsafe locomotion, forming an instrument capable of causing falls 23,[27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…These assistive devices enable functional independence and offer safety and confidence to the elderly, making it easier for them to carry out their daily activities. However, when not indicated or when used inappropriately, they can have the opposite effect and contribute to unsafe locomotion, forming an instrument capable of causing falls 23,[27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that balance efficacy is related to functional fitness (Klima, Newton, Keshner, & Davey, 2012;Woollacott & Shumway-Cook, 2002) and postural control (Arnold & Faulkner, 2009). For example, Klima et al (2012) found that balance efficacy is significantly correlated with balance ability and functional mobility in community-dwelling older men.…”
Section: Research-article2016mentioning
confidence: 99%
“…For example, Klima et al (2012) found that balance efficacy is significantly correlated with balance ability and functional mobility in community-dwelling older men. Other researchers have found aerobic endurance is strongly related to balance efficacy in older adults (Julius, Brach, Wert, & VanSwearingen, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A score of zero represents no confidence, while a score of 100 represents complete confidence in performing the activity. The scale was found reliable in elderly and post-stroke populations [33,34], and is often used as an indication of fear of falling [35].…”
Section: Activities-specific Balance Confidence (Abc) Scalementioning
confidence: 99%